2021
DOI: 10.3390/biomedicines9101370
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and the Kidney: A Review

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with several extrahepatic manifestations such as cardiovascular disease and sleep apnea. Furthermore, NAFLD is reported to be associated with an increased risk of incident chronic kidney disease (CKD). Inflammation and oxidative stress are suggested to be the key factors involved in the inflammatory mechanisms and pathways linking NAFLD to CKD and are responsible for both the pathogenesis and the progression of CKD in NAFLD patients. This review aims to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…NAFLD, one of the most common liver diseases, is a strong risk factor for chronic kidney disease (CKD) [ 41 , 42 ]. Liver-related portal inflammation [ 43 ] and portal hypertension can trigger a subclinical hepatorenal reflex, which over time may contribute to the development and progression of CKD [ 44 ]. Further mechanistic studies are needed in this area to better understand the interrelationship between liver regeneration, eGFR, CYP1A2 activity, and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD, one of the most common liver diseases, is a strong risk factor for chronic kidney disease (CKD) [ 41 , 42 ]. Liver-related portal inflammation [ 43 ] and portal hypertension can trigger a subclinical hepatorenal reflex, which over time may contribute to the development and progression of CKD [ 44 ]. Further mechanistic studies are needed in this area to better understand the interrelationship between liver regeneration, eGFR, CYP1A2 activity, and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that fatty liver disease was strongly associated with the high risk of developing chronic kidney disease (CKD). 2,3 However, the proportion of patients concurrent with fatty liver disease was not provided in the study, and further subgroup analysis in patients with and without fatty liver disease would provide more information about the association between NUCs and CKD.…”
Section: Editorsmentioning
confidence: 99%
“…Inflammation and oxidative stress are suggested to be the key factors involved in the inflammatory mechanisms and pathways linking NAFLD to CKD and responsible for both the pathogenesis and the progression of CKD in patients with NAFLD. 7 It could also be attributed to co-existing co-morbidities, for instance, uncontrolled DM which can in itself lead to glomerulosclerosis and the development of diabetic nephropathy. Other risk factors might include the presence of obesity and hypertension.…”
Section: Introductionmentioning
confidence: 99%